Comparison between nurse anesthetists and anesthesiology residents of blood pressure management during general anesthesia: a retrospective analysis using an electronic anesthesia record database - Arisa Fujii; Marie Miyamori; Hirokazu Shiba; Takeru Abe; Hiromasa Kawakami; Hitoshi Sato; Takahisa Goto (BMC Anesthesiology)
Abstract Background Several Japanese educational institutions have begun to train nurse anesthetists. They manage the patient consistently from pre-operation to post-operation in collaboration with the anesthesiologist. This has helped improve the quality of anesthetic management in an anesthesiologist shortage environment in Japan. However, no studies have examined the quality of anesthetic management by nurses worldwide. Therefore, this study investigated the quality of anesthesia among novice anesthesiology residents and nurse anesthetists, focusing on blood pressure control. Methods This study included adult patients undergoing breast surgery. Nurse anesthetists or anesthesiology residents oversaw general anesthesia. Intraoperative electronic medical records were used to compare the general anesthesia management of nurses and residents. The primary outcome was the sum of the duration during which the mean blood pressure was < 65 mmHg. This was quantified as a percentage of the total anesthesia time (time under mean 65 mmHg: TUm65). Independent variables included patient demographic characteristics, clinical information, the percentage decrease from baseline in the lowest mean blood pressure during anesthesia, and the hourly infusion volume. Results No significant difference was observed in the TUm65 (nurse anesthetists vs. anesthesiology residents: median [IQR] 11.3% [3.3–20.7] vs. 18.1% [5.3–24.0], p = 0.078). No significant differences were noted between nurses and residents concerning the other outcomes. Conclusion No significant differences were observed in the intraoperative blood pressure control between the nurse anesthetists and anesthesia residents.